209k views
4 votes
Find the average rate of change of h(x) = - x ^ 2 + 3x + 3 from x = 2 to x = 6 .

User Torongo
by
4.4k points

1 Answer

6 votes

Answer:

The average rate of change is

Δy ÷ Δx = -20 ÷ 4

Δy/Δx = -20/4

= -5

Explanation:

Given the function


h\left(x\right)\:=\:-x^2\:+\:3x\:+\:3

Putting x = 6


h\left(6\right)\:=\:-\left(6\right)^2\:+\:3\left(6\right)\:+\:3


=-36+18+3


=-15

Putting x = 2


h\left(2\right)\:=\:-\left(2\right)^2\:+\:3\left(2\right)\:+\:3


= -4 + 6 +3


= 5

The change in y from 2 to 6 is

Δy = -15 - 5

= -20

The interval from 2 to 6 has a width of

Δx = 6 - 2

= 4

Therefore, the average rate of change is

Δy ÷ Δx = -20 ÷ 4

Δy/Δx = -20/4

= -5

User Giovanni Funchal
by
4.6k points